Construction and optimization of the watershed-scale ecological network based on network characteristic analysis: A case study of the Lancang River Basin - Yi Wang; Xiaogang Zhou; Chang Ding; Wenxuan Li; Linyun Huang; Beichen Ge; Yuhong Song (Ecological Indicators)
The growth of socio-economic development and human activities markedly threatens the ecological security of river basins. Establishing a robust ecological network (EN) is a viable solution to this problem. Nonetheless, optimizing the structure and stability of ENs remains a complex issue. This study focused on the Lancang River Basin, identifying ecological corridors and critical ecological regions through circuit theory to develop the EN of the Lancang River Basin. Subsequently, complex network theory was utilized to compare the optimization effects of various strategies on the EN, proposing effective optimization methods for the study area. The findings revealed that (1) the EN of the Lancang River Basin comprised 26 ecological sources, 43 ecological corridors, and 106 key ecological regions. (2) The EN was enhanced by incorporating 12 corridors using the low-degree-first (LDF) strategy and the low-betweenness-first (LBF) strategy. Both strategies resulted in substantial improvements in average degree, network diameter, and average path length. (3) Under scenarios of random and deliberate attacks, the LDF strategy proved superior in augmenting overall network performance and bolstering network stability. The optimized network effectively addressed the ecological deficiencies in the Weiyuan River region. This research explored the utilization of complex network theory in EN optimization and provided a foundation for ecological spatial planning and protection policies in the Lancang River Basin.